Debatable Topics in PCOS Patients 2018
DOI: 10.5772/intechopen.73298
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes and Weight Loss: Effects in PCOS

Abstract: Even though controversies surrounding the polycystic ovary syndrome are not yet close to be solved, its clinical manifestations are well known-insulin resistance and obesity, hirsutism, irregular and anovulatory menstrual cycles. The treatment of polycystic ovarian syndrome (PCOS) is mainly symptomatic as its etiology is not yet clear. Lifestyle changes are the primary therapy in overweight and obese women with PCOS. According to majority of the studies, lifestyle changes are the most efective form of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(64 reference statements)
0
2
0
1
Order By: Relevance
“…The composition and effectiveness of the lifestyle modification programmes were analysed through a systematic review. Lifestyle modification is considered the primary treatment for women with PCOS who are obese or overweight (Ionescu et al, 2018), and it is expected to control upper‐body obesity even if the women are not obese or overweight (Sam, 2007), improving their metabolic, reproductive and psychological features (Domecq et al, 2013; Lim et al, 2013; Moran et al, 2011). Hence, a mobile application for lifestyle modification is considered suitable for both obese and normal‐weight groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and effectiveness of the lifestyle modification programmes were analysed through a systematic review. Lifestyle modification is considered the primary treatment for women with PCOS who are obese or overweight (Ionescu et al, 2018), and it is expected to control upper‐body obesity even if the women are not obese or overweight (Sam, 2007), improving their metabolic, reproductive and psychological features (Domecq et al, 2013; Lim et al, 2013; Moran et al, 2011). Hence, a mobile application for lifestyle modification is considered suitable for both obese and normal‐weight groups.…”
Section: Discussionmentioning
confidence: 99%
“…International evidence-based guidelines emphasise the importance of weight management in women with PCOS, which recommends a reduced dietary caloric intake and gradual increase in physical activity (Teede et al, 2018). A previous study has reported that lifestyle modifications are the most effective treatment for losing weight, improving insulin sensitivity, and reducing the incidence of metabolic syndrome and type 2 diabetes (Ionescu et al, 2018). Other recent systematic reviews have also indicated that overweight or obese women with PCOS are expected to experience improvements in obesity or oligo-anovulation owing to lifestyle modifications women (Kim et al, 2020;Lim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…41 Zmniejszenie masy ciała (zaledwie o 5-10% wyjściowej) pozwala na obniżenie stężenia insuliny oraz ograniczenie hiperandrogenizmu w tej grupie pacjentek. 42 W przeglądzie systematycznym i metaanalizie autorstwa Haqq et al dowiedziono, że stosowanie diety ubogoenergetycznej i aktywności fizycznej poprawia stężenie hormonu folikulotropowego (ang. follicle-stimulating hormone -FSH), globuliny wiążącej hormony płciowe (ang.…”
Section: Wybrane Modyfikacje Stylu żYcia W Pcosunclassified